Information Literacy Self-Efficacy of Information Technology Students in Eastern Mediterranean University (EMU) - Farinola, Toochi Priscilia (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Information literacy is the basis for lifelong learning, and it can also be seen as a set of cognitive and practical skills and like any other science, proper training is needed, and standard-based education is definitely better and evaluation would be easier. Information literacy skills, especially for the student in an environment that is full of information from multiple technologies are being developed is equally important. This study aimed to investigate and evaluate the information literacy self-efficacy (ILSE) of Information Technology undergraduate students at Eastern Mediterranean University. Furthermore, this research would create awareness for educationalist and help to recognize individuals with low self-efficacy of the expressed idea based on gender, age and study level, which may serve as a limiting factor for them to penetrate into their information literacy skills. The quantitative research method was employed in order to collect the data. Hence, the data were collected from 130 participants through the questionnaire in order to evaluate the students’ information literacy self-efficacy. The data were analyzed through SPSS software, version 22. Moreover, descriptive analysis, independent sample t-Test, and one-way ANOVA tests were used for evaluating the obtained data. The findings specify that there is a remarkable statistically significant difference on male and female students ILSE skills. Also, the results indicate that out of the three levels of Information Literacy Skills (ILS), Basic Information Literacy Skills (BILS) has the highest percentage compared to Intermediate and Advanced Information Literacy Skills (IILS and AILS). However, there is a significant difference in how students define and locate the information they need based on their study level and age. Finally, the study showed that students’ information literacy skills as the greatest impact were on increasing the ability to access information. Keywords: Information literacy, Information literacy skills, self-efficacy, information literacy self-efficacy, Undergraduate students.

ÖZ : Bilgi okuryazarlığı hayat boyu öğrenmenin temelini oluşturur ve aynı zamanda bilişsel ve pratik beceriler kümesi olarak ve başka herhangi bir bilim gibi, uygun eğitime ihtiyaç duyulabilir. Bilgi okuryazarlığı özellikle de öğrencilerin birden fazla teknolojiden elde edinilen bilgilerinin bulunduğu bir ortamda becerilerini geliştirilmeri açısından önemlidir. Bu çalışma, Doğu Akdeniz Üniversitesi'nde Bilgi Teknolojisi lisans öğrencilerinin bilgi okuryazarlığı öz-yeterlik düzeylerini (ILSE) araştırmayı ve değerlendirmeyi amaçlamıştır. Ayrıca, bu araştırma, eğitimciler için bir farkındalık yaratacak ve bilgi okuryazarlığı becerilerine nüfuz etmede sınırlayıcı bir faktör görevi görebilecek, cinsiyete, yaşa ve çalışma düzeyine dayalı ifade edilen düşünceyi düşük özyeterlikli bireyleri tanımaya yardımcı olacaktır. Verilerin toplanması için niceliksel araştırma yöntemi kullanılmıştır. Bu nedenle, öğrencilerin bilgi okuryazarlığı öz-yeterlik düzeylerini değerlendirmek için 130 katılımcıdan elde edilen veriler anket yoluyla toplanmıştır. Veriler SPSS yazılımı, versiyon 22 ile analiz edilmiştir. Elde edilen verilerin değerlendirilmesinde betimsel analiz, bağımsız örnek t-Testi ve tek yönlü ANOVA testleri kullanılmıştır. Bulgular, erkek ve kız öğrencilerin ILSE becerileri üzerinde istatistiksel olarak önemli bir farkın var olduğunu belirtmektedir. Ayrıca sonuçlar, Bilgi Okuryazılığı Becerileri'nin (ILS) üç seviyesinden Temel Bilgi Okuryazlık Becerileri'nin (BILS) Orta ve İleri Düzey Bilgi Okuryazilik Becerileri (IILS ve AILS) ile karşılaştırıldığında en yüksek yüzdeye sahip olduğunu göstermektedir. Bununla birlikte, öğrencilerin çalışma düzeyine ve yaşına dayalı olarak ihtiyaç duydukları bilgiyi nasıl tanımladığı ve yerleştirdikleri konusunda önemli bir fark bulunmaktadır. Son olarak, çalışma, öğrencilerin bilgi okuryazarlığı becerilerinin en büyük etkisi olduğu bilgiye erişme yeteneğini arttırdığını göstermiştir. Anahtar Kelimeler: Bilgi okuryazarlığı, Bilgi okuryazarlığı becerileri, öz-yeterlik, bilgi okuryazarlığı öz-yeterlik, Lisans öğrencileri.
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technologies, 2018. Co-Supervisor: Prof. Dr. Mustafa İlkan and Supervisor: Assist. Prof. Dr. Alper Doğanalp.
Keywords: Information and Communication Technologies in Education; Education - Computer network resources--Educational Technology; Schools--Teaching, Aids and Devices; Educational Technology--Educational Media--E-Learning; Teaching Aids--Teaching Materials--Teaching Equipments--Instructional materials; Teaching - Computer network resources; Information literacy; Information literacy skills; self-efficacy; information literacy self-efficacy; Undergraduate students; Computer Education and Instructional Technologies